Man of the People : The Life of John McCain - Alexander, Paul 1955- (Hoboken John Wiley & Sons, Inc., 2003)
A biography of Senator John McCain, examining his life and accomplishments in the context of late twentieth-century American politics, discussing his formative years as the son and grandson of four-star admirals, his experiences as a prisoner of war in Vietnam, his decision to pursue a political career, and his bid to be the Republican candidate for president in 2000.
Include Notes and Index
Keywords: United States -- McCain, John, 1936- -- Legislators -- United States. Congress. Senate